VD_FINDINFO Jug / 2020 / 322 vom 15. Januar 2020 - VD Tribunal cantonal (2020)
MENACEDROIT PÉNAL, INFRACTION QUALIFIÉE, SURSIS À L'EXÉCUTION DE LA PEINE, ADMISSION PARTIELLE | 180 al. 1 CP, 42 al. 1 CP, 44 al. 1 CP, 44 al. 2 CP, 47 CP